TAWAKKAL SEBAGAI SUMBER KEBAHAGIAAN HIDUP Telaah Pemikiran Badiuzzaman Said Nursi dalam al-Kalimāt aṣ-Ṣhaghirah fil-‘Aqīdah wal-‘Ibādah - Muhammad Iqbal Rahman (ISLAMIDA Journal of Islamic Studies, 2022)
Abstract This article attempts to describe Said Nursi's thoughts on tawakkal as a source of happiness in al-Kalimat aṣ-Ṣhaghirah fil-'Aqīdah wal-'Ibādah. This reflection is present because humans as poor and helpless (inferior) creatures need provisions to face the uncertainties life. What humans do and strive for does not always run smoothly, sometimes they meet failure and failure in turn weakens humans. Leaning on others brings nothing but regret and disappointment. Being leaning on a higher (God, superior), although criticized for being the cause of the decline of the times, in fact can be a very strong foundation for those who believe in it. The main question in this paper is "How can tawakkal in Said Nursi's mind be a source of happiness in life?" The results of this reflection indicate that Said Nursi applies the concept of tawakkal not just theorizing and this paper finds that tawakkal invites someone to act qana'ah, and in qana'ah contains submission to the Almighty. The attitude of qana'ah brings gratitude to a subject, and gratitude then brings happiness. That’s the formulation of tawakkal in picking up happiness.